Study and Assessment of the Efficiency of the Cocoa Bark Extracted from the Theobroma Cacao as an Inhibitor of the Corrosion of Carbon Steel in Substitution of Benzotriazole - Barreto,Lhaira Souza (2018)
Corrosion represents high losses to the economy, therefore, researches on the minimization of its damages in materials, mainly the metallic ones, are necessary. Among the various alternatives of protection against corrosion, there is the application of corrosion inhibitors that can minimize or even stop the corrosive process of metallic materials. However, at present, substances usually used as corrosion inhibitors present high toxicity, being considered harmful components to the environment and to human health. Therefore, there is an urgent need for studies on viable corrosion inhibitors, by considering not only economic but also environmental costs. The present work studied the use of cocoa bark extract (Theobrama cacao L), for possible replacement of benzotriazole (BTAH) in the corrosion inhibition of ASTM 1020 carbon steel (CS- ASTM 1020) in 18.23 g.L-1 hydrochloric acid media. Weight loss measurements, anodic and cathodic potentiodynamic polarization curves and electrochemical impedance experiments were carried out. The results showed that the addition of the extract to the electrolyte effectively hinder the corrosion process and indicated its adsorption on the electrode surface. In addition, the inhibiting efficiency of the cocoa bark extract was only slightly inferior to BTAH, showing that it can be an environmentally friendly option to toxic inhibitors.